Different perspectives : women writing in Bangladesh - Azim, Firdous, 1952-; Zaman, Niaz. (Dhaka : Rachna : University Press Ltd., 1998)
Collection of Bengali short stories, translated into English.
BIED
Complimentary copy from BIED
Keywords: Short stories, Bengali -- Bangladesh -- Translations into English; Bengali fiction -- Women authors -- Translations into English